Economic Warfare and the Sea Grand Strategies for Maritime Powers, C. 1600-1945 - Morgan-Owen, David G. (Research in Maritime History LUP Ser, 2020)
Economic Warfare and the Sea examines the relationship between trade, maritime warfare, and strategic thought between the early modern period and the late-twentieth century. Using a variety of geographic and chronological examples, it presents a longue duree approach to a crucial theme in maritime strategic thought